Seasonal variations in C/N/P/K stoichiometric characteristics in different plant organs in the various forest types of Sygera Mountain - Li, Yueyao; Wang, Jiaxiang; Wang, Luqi (Frontiers in Plant Science, 2024)
We explored the resource acquisition and growth strategies of plants adapting to different environments, focusing on the typical forest types of Sygera Mountain: Pinus armandii, Picea likiangensis var. Linzhiensis, Abies georgei var. Smithii, and Juniperus saltuaria. Then, we analyzed the nutrient content and stoichiometric ratios of C, N, P, and K in different plant organs (leaves, branches, trunks, and roots) to examine the stoichiometric characteristics and nutrient balance mechanisms in these forests. Results show that within the same forest type, different plant organs exhibit high C and low N, P, and K levels. N content in all organs followed the order leaves > branches > roots > trunks. During the growth phase, the concentrations of P and K in PLL and AGS follow the order branches > leaves > roots > trunks. In the dormant phase, the distribution in different organs had the order leaves > branches > roots > trunks. C content remained relatively stable over time. In the same organ across different forest types, increase in nitrogen content in plant leaves is an active adaptation of JS plants, indicating that JS has a conservative growth strategy and can adapt to environmental stress. Owing to the influence of seasons, the evolution process of N and P content fluctuates, allocating nutrients to supporting and transporting organs for resource optimization and allocation. The N and P content were lower in the growth phase than in the dormant phase. Seasonal variations in the C/N, C/P, and C/K ratios in different forests were inversely correlated with changes in N, P, and K content in plant organs, supporting the "growth rate hypothesis." Stoichiometric analysis suggests that different limiting elements exist in organs across various forest types. Principal component analysis indicates that the seasonal patterns of stoichiometric ratios in the organs of different forest types show species-specific characteristics, reflecting the evolutionary nutrient utilization strategies of plant genera. In summary, plant growth in different Sygera Mountain forest types is limited by N and P, with a high tendency toward nitrogen limitation. The nutrient utilization and distribution differences among various organs during different growth stages are primarily